Upaya Kelompok Sadar Wisata (Pokdarwis) dalam Mengembangkan Potensi Lokal Rawa Tirta di Desa Sumberkedawung Kecamatan Leces Kabupaten Probolinggo - Mubarog, Husni; Wardatus Sholeha, Alvia (STISIPOL Raja Haji, 2022)
Local potential is an invaluable advantage of a region or area. Pokdarwis is one of the managers who come from the community and of course has a strategic role in developing the potential of natural and cultural wealth owned by an area to become a tourist destination, especially in Sumberkedawung Village, Leces District, Probolinggo Regency. Therefore, Pokdarwis efforts in developing local potential through Rawa Tirta to become a tour. The purpose of this study was to analyze and determine the efforts of Pokdarwis in developing the local potential of Rawa Tirta in Sumberkedawung Village, Leces District, Probolinggo Regency. This study uses descriptive qualitative research methods, the research location is in Sumberkedawung Village, Leces District, Probolinggo Regency, the data sources used in this study are primary data sources and secondary data sources, while data collection techniques are through observation, interviews and utilization of literacy sources from media. The results of this study indicate that Pokdarwis' efforts in developing the local potential of the Tirta Swamp have been running as expected by clearing some of the Tirta Swamp from the water hyacinth plant and the availability of canoes and boats. Pokdarwis efforts in the development of Rawa Tirta must be improved again, so that the development of Rawa Tirta tourism continues in accordance with the Pokdarwis plan, Sumberkedawung Village, Leces District, Probolinggo Regency. Keywords: Development, Pokdarwis, Local Potential.